(untitled) (Faridpur Medical College Journal, 2011)
Infantile hypertrophic pyloric stenosis (IHPS) is the most common cause of gastric outlet obstruction in infants which needs surgical treatment. The aim of this study was to review the management of IHPS in our hospital to compare with other developed centers. This is a prospective analytical study carried out in the Department of Pediatric Surgery, Faridpur Medical College Hospital and Dr. Zahed Children Hospital at Faridpur, during the period of May 2002 to October 2010. Total 77 patients were treated by Ramstedt’s pyloromyotomy after proper diagnosis and resuscitation. The male to female ratio was 10:1. Most of the patients presented to us within 40 days of age (90%).Younger one was 15 days and elder one was 69 days. In all cases diagnosis were done on clinical basis. The diagnosis is confirmed by barium meal x-ray in 71 cases and sonogram in 15 cases. Serum electrolytes were not estimated in all patients. There was moderate to severe dehydration in more than 60% cases. 71 cases were operated under general anesthesia and 06 cases were operated with local anesthesia. There was one postoperative death on 4th post-operative day. Oral feeding started after 8 to 10 hours postoperatively in all cases. Mucosal perforation occurred in 1 case and that was recognized and treated conservatively without any ill effect. Superficial wound infection encountered in 3 cases. Early diagnosis, preoperative correction of dehydration and electrolyte imbalance and experiences of surgeons play important role for management of IHPS. Key words: IHPS; Pyloromyotomy; Dehydration; Local anesthesia; Mucosal perforation. DOI: 10.3329/fmcj.v6i1.7401 Faridpur Med. Coll. J. 2011;6(1): 02-04